Nodule worm infection in humans and wild primates in Uganda: cryptic species in a newly identified region of human transmission. - Ria R Ghai; Colin A Chapman; Patrick A Omeja; T Jonathan Davies; Tony L Goldberg (Public Library of Science (PLoS), 2014)
Soil-transmitted helminths (STHs) are a major health concern in tropical and sub-tropical countries. Oesophagostomum infection is considered endemic to West Africa but has also been identified in Uganda, East Africa, among primates (including humans). However, the taxonomy and ecology of Oesophagostomum in Uganda have not been studied, except for in chimpanzees (Pan troglodytes), which are infected by both O. bifurcum and O. stephanostomum.We studied Oesophagostomum in Uganda in a community of non-human primates that live in close proximity to humans. Prevalence estimates based on microscopy were lower than those based on polymerase chain reaction (PCR), indicating greater sensitivity of PCR. Prevalence varied among host species, with humans and red colobus (Procolobus rufomitratus) infected at lowest prevalence (25% and 41% by PCR, respectively), and chimpanzees, olive baboons (Papio anubis), and l'hoest monkeys (Cercopithecus lhoesti) infected at highest prevalence (100% by PCR in all three species). Phylogenetic regression showed that primates travelling further and in smaller groups are at greatest risk of infection. Molecular phylogenetic analyses revealed three cryptic clades of Oesophagostomum that were not distinguishable based on morphological characteristics of their eggs. Of these, the clade with the greatest host range had not previously been described genetically. This novel clade infects humans, as well as five other species of primates.Multiple cryptic forms of Oesophagostomum circulate in the people and primates of western Uganda, and parasite clades differ in host range and cross-species transmission potential. Our results expand knowledge about human Oesophagostomum infection beyond the West African countries of Togo and Ghana, where the parasite is a known public health concern. Oesophagostomum infection in humans may be common throughout Sub-Saharan Africa, and the transmission of this neglected STH among primates, including zoonotic transmission, may vary among host communities depending on their location and ecology.